Review article: reflections on international labour studies in the UK. (1st April 2008) - Peter Waterman,
Abstract : Reflecting personally on the contribution of the UK to international labour studies over the past forty years and his own role in this history, Peter Waterman reviews some recent publications and websites from both inside and outside the official trade union movement. These are: Tony Pilch (ed) Trades Unions and Globalisation, London: Smith Institute. 86 pp. ISBN 1-905370-14-8 Sheila Cohen, Ramparts of Resistance: Why Workers Lost Their Power and How to Get it Back, London: Pluto, 248 pp. ISBN 13-978-0-7453-1529-4 (pb) Ronaldo Munck, 2006. Globalisation and Contestation: The Great Counter-Movement, London: Routledge. 176 pp. ISBN-10 0415376564 Angela Hale and Jane Wills (eds). Threads of Labour: Garment Industry Supply Chains from the Workers' Perspective, Oxford: Blackwell, 288 pp. ISBN-10: 1405126388 Paul Mason, Live Working or Die Fighting: How the Working Class Went Global, London: Harvill Secker. 304 pp. ISBN 978-0-436-20615-3 NewUnionism http://www.newunionism.net/ Union Ideas Network http://www.uin.org.uk/